The Indian nation in 1942 - Pandey, Gyanendra, 1949-; Centre for Studies in Social Sciences (Calcutta : Published for Centre for Studies in Social Sciences, Calcutta by K.P. Bagchi, 1988)
On the Quit India Movement, 1942; contributed articles.
Includes bibliographies and index.
Keywords: India -- History -- Quit India movement, 1942.